Artistic and stylistic peculiarities of the Cossack fairy tales of the Dnieper region (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
This article for the first time describes artistic and figurative structure of Cos-sack’s fairy tales of the central and lower parts of the Dnipro banks. It is defined that it is a separate genre type of fairy-tale epos, which is distinguished by poetic means, plot and thematic peculiarities of its functioning.
Keywords: fairy tale; Cossack’s fairy tale